CICS: Cloud–Internet Communication Security Framework for the Internet of Smart Devices - Alam, Tanweer; Benaida, Mohamed (International Journal of Interactive Mobile Technologies (iJIM), 2018)
The internet of smart devices is a network of intelligent gadgets with sensors, programs, Wi-Fi and communication network connections. These devices store the data in cloud and process data outside the device using the proposed Cloud-Internet communication framework. These devices can communicate with other devices using the proposed framework. However, there are many challenges for communication security among the internet of smart devices. The Cloud can store the device data with security, reliability, privacy and service availability. The communication Security has been raised as one of the most critical issues of cloud computing where resolving such an issue would result in a constant growth in the use and popularity of cloud computing. Our purpose of this study is to create a framework for providing the communication security among smart devices network for the internet of things using cloud computing. Our main contribution links a new study for providing communication security for the internet of smart devices using the cloud-Internet framework. This study can be helpful for communication security problem in the framework of the Internet of Things. The proposed study generates a new framework for solving the issue of communication security among internet of smart devices.